Cost of healthcare rehabilitation services following road traffic injuries: Results from a Level-I trauma center in Saudi Arabia - Suliman Alghnam; Meshal M Alqahtani; Hosam A Alzahrani; Abdulfattah S Alqahtani; Ibrahim T Albabtain; Khalid A Alsheikh; Mohamed K Alatwi; Mohamed A Alkelya (Wolters Kluwer Medknow Publications, 2022)
BACKGROUND: Road traffic injuries (RTIs) are the second leading cause of mortality in Saudi Arabia. The high rate of RTIs puts a strain on rehabilitation services. Yet, little is known of the economic burden of nonfatal RTIs and rehabilitation services. This study, therefore, aims to describe the annual rehabilitation costs associated with RTIs at a local trauma center. MATERIALS AND METHODS: This study was conducted among all the 17 years or older patients hospitalized at King Abdulaziz Medical City in Riyadh following RTIs and required rehabilitation care. We included 299 patients who met the inclusion criteria and were followed for one year after discharge from the index hospital. The data was abstracted through retrospective review of patients' medical records. All rehabilitative services utilized by the healthcare system were recorded. To describe the economic burden, the mean, median, standard deviation, and interquartile range (IQR) were calculated. Total costs were aggregated for all patients to estimate overall costs. RESULTS: The study population was relatively young (31 years ± 14.4). The total annual rehabilitation cost of patients was Saudi Riyals (SAR) 6,113,781 (IQR: 20,589.3 − 3,125 = 17,464.3), and the average for each patient was SAR 20,447 (median = 7875). Patients aged 40-59 years and ≥60 years accounted for the highest average rehabilitation cost of SAR 31,563.99 and 32,639.21, respectively. Rehabilitation visits incurred the highest cost (mean SAR 1,494,124), followed by bed utilization which cost SAR 1,311,972 and radiology examination at SAR 1,032,261. The cost of motorcycle injuries was relatively higher (SAR 44,441.0) than other injury mechanisms. CONCLUSION: This study underlines the economic burden of rehabilitation services resulting from RTIs. Public health interventions are needed to reduce the burden of RTIs by dealing with their preventable causes and improving road safety measures. These findings may be useful to policymakers and researchers to support and improve rehabilitation services in Saudi Arabia.